2005
DOI: 10.1093/rheumatology/keh407
|View full text |Cite
|
Sign up to set email alerts
|

Hypocomplementaemia as an immunological marker of morbidity and mortality in patients with primary Sjogren's syndrome

Abstract: Hypocomplementaemia is closely associated with systemic expression and adverse outcomes (lymphoma development and death) in patients with primary SS. Our results support the inclusion of complement determination at diagnosis as a predictor of the outcome of patients with primary SS and its routine determination in the clinical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 20 publications
5
110
3
Order By: Relevance
“…As observed for HCV infection, the prevalence of other virus-related MC seems to show a variable prevalence among patient's series from different geographical areas [86]. Moreover, a number of clinicoepidemiological studies revealed a heterogeneous distribution of different HCV-related extra hepatic manifestations, including some autoimmune disorders such as 'primary' Sjogren's syndrome [87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…As observed for HCV infection, the prevalence of other virus-related MC seems to show a variable prevalence among patient's series from different geographical areas [86]. Moreover, a number of clinicoepidemiological studies revealed a heterogeneous distribution of different HCV-related extra hepatic manifestations, including some autoimmune disorders such as 'primary' Sjogren's syndrome [87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Cryoglobulinemic syndrome may share a number of etiopathogenetic events and clinical features with both autoimmune diseases such as autoimmune hepatitis, Sjö-gren's syndrome, and polyarthritis, and B-cell lymphomas [3,11,12,25,28,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. Therefore, a differential diagnosis should be carefully done in all patients with MC syndrome (Fig.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 3 more Smart Citations